2020
DOI: 10.1101/2020.06.13.20130252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of IgG antibodies to SARS-CoV-2 in Wuhan – implications for the ability to produce long-lasting protective antibodies against SARS-CoV-2

Abstract: Background It is to be determined whether people infected with SARS-CoV-2 will develop long-term immunity against SARS-CoV-2 and retain long-lasting protective antibodies after the infection is resolved. This study was to explore to explore the outcomes of IgG antibodies to SARS-CoV-2 in four groups of individuals in Wuhan, China. Methods We included the following four groups of individuals who received both COVID-19 IgM/IgG tests and RT-PCR tests for SARS-CoV-2 from February 29, 2020 to April 29, 2020: 147… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 40 publications
7
45
1
1
Order By: Relevance
“…We assumed in our model that there is a long-lasting protective immunity following infection which is consistent with previous human coronavirus types [29,30,32]. However, a recent study suggested that people are unlikely to produce long-lasting protective antibodies against this virus [41]. If, indeed, a rapid waning is possible, this highlights the importance to protect the elderly in regions of high outbreaks.…”
Section: Discussionsupporting
confidence: 67%
“…We assumed in our model that there is a long-lasting protective immunity following infection which is consistent with previous human coronavirus types [29,30,32]. However, a recent study suggested that people are unlikely to produce long-lasting protective antibodies against this virus [41]. If, indeed, a rapid waning is possible, this highlights the importance to protect the elderly in regions of high outbreaks.…”
Section: Discussionsupporting
confidence: 67%
“…This agrees with findings by others. For example, Wu et al have shown that a small but significant number of patients recovered from COVID-19 lack SARS-CoV-2-neutralizing antibodies 63 , and that Liu et al have found similar mortality risks between those COVID-19 patients who tested positive for IgG antibodies against SARS-CoV-2 and those who lacked antibodies against SARS-CoV-2 64 . Therefore, those recovered patients with XLA, ARA, or CVID must have an activated T-cell immunity against SARS-CoV-2 virus.…”
Section: Discussionmentioning
confidence: 99%
“…"Serosurvey" efforts, aimed at determining overall exposure and seroconversion rates in a population, provide a tool to identify exposure associated risk factors and can guide the rational utilization in a health care setting of personal protective equipment (PPE), in addition to return to work policies and providing psychological support to health care workers who are at risk of secondary mental health issues due to overwork and fear of contagion 8 . Although serological studies have been extensively used to determine local epidemic dynamics and population infection fatality rates, significant gaps persist in the current understanding of the humoral responses to SARS-CoV-2 in individuals with asymptomatic infections, with recent evidence suggesting that asymptomatic individuals may have a weaker humoral immune response to SARS-CoV-2 infection and an early reduction in antibody levels [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%